Peran Direktorat Jenderal Bea dan Cukai dalam Melakukan Pengawasan terhadap Pelaksanaan Sistem National Single Window (NSW) di Tanjung Priok Tahun 2010- 2012 dalam Rangka Mendukung Proses Pembentukan Komunitas Ekonomi ASEAN (ASEAN Economic Community/AEC) - Morina Sandra; Tri Cahya Utama; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
This research analyzes and explain implementation of National SingleWindow System (NSW) at Port of Tanjung Priok related to import license andmonitoring process undertaken by Directorate Customs and Excise in implementationof the system. In 2015 will officially formed ASEAN Economic Community, whereNSW System is one thing that support the community by using that system asinfrastructure to facilitating import licensing and improving supervision in importtraffic. Before NSW System applied, process of import license is manually and willspend time in days. The problem is how is the process of import license in NSWSystem? How DJBC monitoring the import traffic after NSW System in Port ofTanjungPriok applied?In this research, researcher used qualitative descriptive approach. ThisResearch was conducted in Directorate Customs and Excise Office, East Jakarta.The data was collected from interviewing with Yan Inderayana and Tri Wahyudi asofficial and interviewing with importer who use NSW System, moreover the datacollected from document.NSW System is electronic system that used one way for facilitate trading andinformation of import-export in ASEAN. Applying NSW System as effort to facilitatetrading in ASEAN in order to easier and speeding the trading traffic.Whilesurveillance under taken by DJBC for minimalize import smuggling and bribery isEarly Warning Systems and formed Employee Complaint Line. DJBC have beendoing the system as procedure, but in monitoring we can still get import smugglingand bribery caused by bad importer and attitudes and behavior of the employee isless discipline.Key words: Directorate Customs and Excise, NSW System, Port of Tanjung Priok